Executive Compensation and Firm Performance: A Cross-industry Analysis - Mohanty, Dr. Ayasa Kanta; Yamuna , Dr.D.; Harinaiha , Adarsha; Sharma, Prabhat; Ahluwalia , Gunveen; Anjuly, Dr.; Hafiz , Dr. Ansari Mehrunnisa (International Journal of Accounting and Economics Studies, 2025)
Executive compensation has been of great interest to financial economists for a long time. The topic of executive remuneration is rich, complicated, and divisive. Besides there being fierce argument among scholars about its causes, the effectiveness of existing methods, and the argument for reform, few subjects have generated such popular interest. Politicians, regulators, investors, and chief executives themselves have all taken a firm stance on whether and how to change pay. Firm performance is one of the most highly visible ideas in organizational research. Despite its significance, and in spite of the numerous developmental criticisms over the years, performance remains a troublesome construct upon which to operationalize in a scientifically strict sense. Following identification of three arguably useful strategies for conceptualizing performance, we see that most research is internally conflicted in application of these approaches, a scenario that results in significant trouble interpreting research effectively. The central cause of incoherence results from the simultaneous utilization of an abstract conceptualized view of performance as a common variable in the building of theories (the latent multidimensional approach) and implementation of one or two limited definitions of performance as used in empirical work (the separate constructs approach). Follow-up investigations aimed at specifying the optimal route to resolving these mismatches suggest that our discipline’s extensive employment of abstract performance in theory-making is not empirically supported and must be replaced by more concrete features of performance to align with current practices in empirical research. While altering would significantly impact the field and would be resisted by numerous practitioners, it presents a tangible course away from indefensible practices. It turns out that higher compensation, especially when it comes to bonuses and equity incentives, is associated with improved performance in companies. This insight comes from a thorough analysis across various industries looking at executive pay and how it relates to firm performance. It aligns perfectly with the idea that linking executive salaries to performance encourages them to focus on boosting shareholder value. However, the empirical findings suggest that the direct relationship between executive compensation and firm performance is statistically insignificant (p = 0.981). This indicates that while compensation structures are designed with performance in mind, other contextual or firm-specific factors may mediate this relationship.